2017
DOI: 10.1111/bcpt.12718
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibiting Nuclear Factor‐kB Ameliorates Oxidative Stress and Suppresses Renal Inflammation in Early Stage of Alloxan‐Induced Diabetic Nephropathy in Rat

Abstract: Diabetic nephropathy is one of the major microvascular complications of diabetes mellitus which ultimately gives rise to cardiovascular diseases. Prolonged hyperglycaemia and chronic renal inflammation are the two key players in the development and progression of diabetic nephropathy. Nuclear factor kB (NF-kB)-mediated inflammatory cascade is a strong contributor to the renovascular inflammation in diabetic nephropathy. Here, we studied the effects of piceatannol, a potent NF-kB inhibitor, on various oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Our results showed that AP was able to alter the concentration of the albumin in the serum of diabetic rats after 30 days, suggesting that AP might potentiate the systemic effects of diabetes. These effects, especially diabetic nephropathy, occur rapidly in the rat model (30) and differ from the reality of the development of diabetes in humans (19).…”
Section: Discussionmentioning
confidence: 96%
“…Our results showed that AP was able to alter the concentration of the albumin in the serum of diabetic rats after 30 days, suggesting that AP might potentiate the systemic effects of diabetes. These effects, especially diabetic nephropathy, occur rapidly in the rat model (30) and differ from the reality of the development of diabetes in humans (19).…”
Section: Discussionmentioning
confidence: 96%
“…It was reported that miR-150-3p could be induced by NF-kB activation [ 43 ]. Considering the important roles of NF-kB pathway in oxidative stress response and inflammation [ 44 ], investigating the underlying interaction between NF-kB and miR-150-3p will be of particular interest to study the molecular mechanisms of oxidative stress response in liver carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic patient, increased AGEs and ROS burden activates leukocytes that release superoxide radicals and proteases in the kidney ( Mohamed et al, 1999 ; Patel and Santani, 2009 ). Additionally, leukocytes up regulate transcription of NF-κβ in endothelial and mesangial cells ( Sanz et al, 2010 ; Silva et al, 2011 ; Borgohain et al, 2017 ).…”
Section: Nf-κβ and Diabetic Nephropathymentioning
confidence: 99%